A Case Study of Positive Behavior Supports-Based Interventions in a Seventh-Grade Urban Classroom. Issue 4 (1st October 2016) - Hollingshead, Aleksandra; Kroeger, Stephen D.; Altus, Jillian; Trytten, Joyce Brubaker
Abstract : Struggling with frequent off-task behavior, a teacher in a midwestern inner-city high school requested assistance in her social studies classroom. A study was designed to investigate if a combination of positive behavior supports-based interventions such as behavior-specific praise and reduced teacher reprimands might improve on-task behavior. A classroom-wide, explanatory embedded case study was carried out over three months in a high-poverty urban 7–12 high school. The intervention resulted in increased on-task behavior classwide. Implications for culturally responsive practices for students in an urban classroom setting are discussed.